Pengaruh Problem Based Learning (PBL) Terhadap Keterampilan Berpikir Kritis dan Kolaboratif dalam Pembelajaran Biologi Terintegrasi Nilai Islam - Nova Fauziah Rahman; Listyono; Mirtaati Na'ima (Al-Alam: Islamic Science Education Journal, 2024)
Science and technology in the 21st century are developing very rapidly, one of which is in the field of education. Critical thinking is one of the thinking skills needed in the 21st century (21st Century Skill). Students are not only required to have critical thinking skills, but they also need to have collaborative skills. Based on the initial tests carried out, it is known that the critical and collaborative thinking skills of students at MA Matholi'ul Huda Sokopuluhan Pati are still in the low category, so efforts are needed to improve these skills. However, in its implementation it requires a learning model that can help, namely the problem based learning (PBL) model. The PBL model has a good effect on students if it is applied to science material that is integrated with Islamic values. The aim of this research is to analyze the influence of the PBL model on students' critical and collaborative thinking skills in integrated biology learning with Islamic values. The method used in the research is quasi-experimental with a pretest posttest control group design. The results of the research show that there is an influence of the PBL learning model on students' critical and collaborative thinking skills in biology learning integrated with Islamic values. This is proven by the results of the Anacova test of the critical thinking instrument with a significance value of 0.000, meaning that H1 is accepted. The conclusion in this research is that the PBL learning model can improve students' critical and collaborative thinking skills in integrated biology learning with Islamic values.